Pharmaceutical residues in the ecosystem: Antibiotic resistance, health impacts, and removal techniques - Husain Khan, Afzal; Abdul Aziz, Hamidi; Palaniandy, Puganeshwary; Naushad, Mu; Cevik, Emre; Zahmatkesh, Sasan (Chemosphere (Oxford), 2023)
Hospital wastewater has emerged as a major category of environmental pollutants over the past two decades, but its prevalence in freshwater is less well documented than other types of contaminants. Due to compound complexity and improper operations, conventional treatment is unable to remove pharmaceuticals from hospital wastewater. Advanced treatment technologies may eliminate pharmaceuticals, but there are still concerns about cost and energy use. There should be a legal and regulatory framework in place to control the flow of hospital wastewater. Here, we review the latest scientific knowledge regarding effective pharmaceutical cleanup strategies and treatment procedures to achieve that goal. Successful treatment techniques are also highlighted, such as pre-treatment or on-site facilities that control hospital wastewater where it is used in hospitals. Due to the prioritization, the regulatory agencies will be able to assess and monitor the concentration of pharmaceutical residues in groundwater, surface water, and drinking water. Based on the data obtained, the conventional WWTPs remove 10–60% of pharmaceutical residues. However, most PhACs are eliminated during the secondary or advanced therapy stages, and an overall elimination rate higher than 90% can be achieved. This review also highlights and compares the suitability of currently used treatment technologies and identifies the merits and demerits of each technology to upgrade the system to tackle future challenges. For this reason, pharmaceutical compound rankings in regulatory agencies should be the subject of prospective studies. [Display omitted] •Hospitals are a significant source of increased pharmaceutical wastewater discharges.•More than 90% of PhACs are eliminated in the secondary and advanced stages.•Using advanced technologies to eliminate pharmaceuticals is expensive and energy-intensive.•Considering pharmaceuticals' potential impact on aquatic ecosystems, priority drugs need to be identified.